The Testament politique of Nicholas I?: Monarchical propaganda and the birth of a national collection - Sopo Elina (Oxford University Press, 2022)
This article explores the symbolic function of ritual and collecting during the political rule of Tsar Nicholas I through a close reading of the unpublished letters of the protégés of the emperor who played decisive roles in the Society for the Encouragement of the Culture of the Fine Arts in Finland. It explores how long-established aspects of the psychology of authority and monarchical propaganda were performed and expressed, and how they were deployed in the image creation and governance of the empire. Also addressed are questions about the degree to which the government’s view of Romantic nationalism was ambivalent, and how the essentially ancien régime outlook of an enlightened autocrat came to be reconciled with the radical views of the nationalists.
© The Author(s) 2020. Published by Oxford University Press. All rights reserved.